New Insights in Anorexia Nervosa - Gorwood, Philip; Blanchet-Collet, Corinne; Chartrel, Nicolas; Duclos, Jeanne; Dechelotte, Pierre; Hanachi, Mouna; Fetissov, Serguei; Godart, Nathalie; Melchior, Jean-Claude; Ramoz, Nicolas; Rovere-Jovene, Carole; Tolle, Virginie; et al. (Frontiers in Neuroscience, 2016)
Anorexia nervosa (AN) is classically defined as a condition in which an abnormally low body weight is associated with an intense fear of gaining weight and distorted cognitions regarding weight, shape and drive for thinness. This article reviews recent evidences from physiology, genetics, epigenetics and brain imaging which allow to consider AN as an abnormality of reward pathways or an attempt to preserve mental homeostasis. Special emphasis is put on ghrelino-resistance and the importance of orexigenic peptides of the lateral hypothalamus, the gut microbiota and a dysimmune disorder of neuropeptide signaling. Physiological processes, secondary to underlying and premorbid vulnerability factors - the “pondero-nutritional-feeding basements”- are also discussed.